A multi‐proxy record of abrupt cooling events during the Windermere Interstadial at Crudale Meadow, Orkney, UK. (9th March 2021) - Francis, Christopher P.; Engels, Stefan; Matthews, Ian P.; Palmer, Adrian P.; Timms, Rhys G. O.; Jourdan, Anne‐Lise; Candy, Ian
ABSTRACT: Three clearly defined abrupt cooling events (ACEs) can be observed within Greenland Interstadial (GI)‐1 in the Greenland ice‐core records. However, the spatial variation in amplitude and timing of these ACEs is poorly understood due to the paucity of well‐dated records with quantified temperature reconstructions. This study presents high‐resolution chironomid‐inferred July air temperature (TJul ) and oxygen isotope (δ 18 O) records from Crudale Meadow (Orkney Isles, UK). Three centennial‐scale ACEs punctuate the Windermere Interstadial at Crudale Meadow. The largest ACE shows an amplitude of 5.4 °C and a 1% isotopic decline and is centred on ~14.0 ka bp, consistent with the timing of the GI‐1d event in the Greenland stratigraphy. The two other observed ACEs are of smaller magnitude and are centred on ~13.6 ka bp and ~13.2 ka bp, with these smaller magnitude events tentatively correlated with the GI‐1cii and GI‐1b events, respectively, but lack sufficient chronological constraint to fully assess their timing. When comparing the Crudale Meadow record with other locations in the British Isles a strong relationship can be observed between the magnitude of TJul cooling and latitude, with a reduced signal in more southerly locations, indicating that oceanic forcing may be a key driver of the ACEs.